2017
DOI: 10.4149/km_2017_1_33
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze casting of electromagnetically stirred aluminum matrix nanocomposites in semi-solid condition using hybrid algorithm optimized parameters

Abstract: The government mandated fuel efficiency standards for automobile manufacturers reinforce the incentives to reduce the fuel consumption of their vehicles and minimize CO2 greenhouse emission, which requires developing the lighter vehicles, while preserving product performance and cost objectives. One of the effective means to address this challenge has been the design and application of lightweight materials including AMNCs for the automotive parts. Multiple methods have been introduced to manufacture AMNCs suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, electromagnetic stirrers were further utilised to overcome the problems associated with magnetic stirrers as the economical aspect of mass production was affected. To circumvent this problem, Shamsipour et al utilized electromagnetic stirrers to fabricate aluminium matrix nanocomposites by optimising the parameters which led to superior wear behaviour [24]. Further, study showed the intermetallic particles were evenly dispersed with lower stress concentration points throughout the Al-Si metal matrix when using electromagnetic stirrers [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, electromagnetic stirrers were further utilised to overcome the problems associated with magnetic stirrers as the economical aspect of mass production was affected. To circumvent this problem, Shamsipour et al utilized electromagnetic stirrers to fabricate aluminium matrix nanocomposites by optimising the parameters which led to superior wear behaviour [24]. Further, study showed the intermetallic particles were evenly dispersed with lower stress concentration points throughout the Al-Si metal matrix when using electromagnetic stirrers [25].…”
Section: Introductionmentioning
confidence: 99%
“…ANFIS-PSO algorithm considered for the casting process had resulted in enhancement of the results [21]. Shamsipour et al evaluated the wear behavior of optimized parameters of Al/TiC nanocomposite using ANFIS and PSO techniques [22].…”
Section: Introductionmentioning
confidence: 99%
“…Here G is the elastic shear modulus, x f is the fraction of the external atoms concentration, and ε is the fraction of the difference between the atoms and the atoms dissolved in the diameters [50,51].…”
Section: Introductionmentioning
confidence: 99%